PEMBUATAN DAN PERAWATAN RAMBUT DENGAN RATUS RAMBUT - Ayuningtyas, Nurina; Armandari, Mari Okatini; Silfi Ambarwati, Neneng Siti (LPPM Universitas Negeri Jakarta, 2021)
Having healthy and soft hair is everyone's dream that must be maintained and cared for. For a long time, Indonesian women have been known for their treatments with natural ingredients. The wealth of Indonesia's natural resources is very diverse. The empowerment of women in the economic sector is one indicator of increasing welfare. Women also have a big share in poverty reduction activities through community and group empowerment by carrying out household productive business activities. The problem with partners in this community service program is that the activities are not optimal, because of the members' limited ability and knowledge, and partners do not know how to treat hair using traditional ingredients such as hundred hairs. The implementation method in this training is 1) Field observation, 2) Identification of partner problems and weaknesses, 3) Offering solutions to partners, 4) Product implementation. Implementation is done online by providing knowledge and demonstration of material through video shows. The results of community service activities include several components such as the number of participants, goal achievement, material achievement, material mastery and video quality is very good. In addition, participants are ready to be involved again in similar activities. This partner coaching activity is expected to complement the knowledge and skills in various aspects of family life, as well as meet the needs so as to strengthen the family economy. Abstrak Memiliki rambut yang sehat dan lembut merupakan impian semua orang yang harus dijaga dan dirawat. Sejak dahulu, wanita Indonesia sudah terkenal dengan perawatan dengan bahan yang alami. Kekayaan sumber daya alam Indonesia sangatlah beragam. Keberdayaan perempuan di bidang ekonomi adalah salah satu indikator meningkatnya kesejahteraan. Perempuan juga mempunyai andil besar dalam kegiatan penanggulangan kemiskinan melalui pemberdayaan masyarakat dan kelompok dengan melakukan kegiatan usaha produktif rumah tangga. Permasalahan mitra pada program pengabdian kepada masyarakat ini adalah kegiatan belum optimal, karena keterbatasan kemampuan & keilmuan anggota, juga mitra belum mengetahui perawatan rambut menggunakan bahan tradisional seperti ratus rambut. Metode pelaksanaan dalam pelatihan ini ialah 1) Observasi lapangan, 2) Identifikasi permasalahan dan kelemahan mitra, 3) Penawaran solusi pada mitra, 4) Implementasi produk. Pelaksanaan dilalukan secara daring dengan pemberian pengetahuan dan demonstrasi materi melalui tayangan video. Hasil kegiatan pengabdian pada masyarakat mencakup beberpa komponen seperti jumlah peserta, ketercapaian tujuan, ketercapaian materi, penguasaan materi serta kualitas video sangatlah baik. Selain itu juga peserta siap terlibat kembali dalam kegiatan serupa. Kegitan pembinaan mitra ini diharapkan dapat melengkapi wawasan pengetahuan dan keterampilan dalam berbagai segi kehidupan keluarga, juga memenuhi kebutuhan sehingga memperkuat perkonomian keluarga.